Adoption and Maintenance of Self Seed Sufficiency in Major Cereal Crops in Mid-Western Terai of Nepal - Chaudhary, Ram Das; Yadav, Bisheswar Prasad; Tripathi, Santosh Raj; Poudel, Padam Prasad; KC, Govinda; Yadav, Dinesh Kumar; Singh, Indrapal (International Journal of Applied Sciences and Biotechnology, 2018)
Regional Agricultural Research Station Nepalgunj (RARS/N) has its four major outreach sites in Satbariya Village Development Committee (VDC) of Dang, Betahani VDC of Banke, Mahammadpur VDC of Bardiya, Patharaiya VDC of of Kailali and model village in Mainapokhar VDC of Bardiya district for test and verify the acceptance of new released varieties under farmers’ field condition and provide an opportunity to the farmers to select most suitable variety on their own choice based on performance. Seed was distributed throughout the OR sites and model village for newly released varieties for self seed sufficiency. New most recent varieties of rice and wheat released in the previous year from concerned commodity research programme, National Rice Research Programme (NRRP), Hardinath and National Whear Research Programme (NWRP), Bhairawaha respectively, were selected. The yield attributing characters, total yield, percentage yield used as seed in the next fiscal year were recorded. Response of the participating farmers for various varieties with respect to various attributes of yield and other important criteria for sustainable cultivation were recorded in individual sheet. Agronomic management practices were done according to recommendation practices for particular crop. Rice varieties of Sukkha series adoption rate was increasing trend. Among them Sukkha Dhan 1, Sukkha Dhan 2 and Sukkha Dhan 3 adoption rate was higher. Wheat variety Gautam adoption rate was higher followed by NL 971. Int. J. Appl. Sci. Biotechnol. Vol 6(1): 38-44